Enhanced removal performance of zero-valent iron towards heavy metal ions by assembling Fe-tannin coating. (1st October 2022) - Feng, Jing; Lang, Gang; Li, Tingting; Zhang, Jing; Li, Tengyue; Jiang, Zhenju
Abstract: Heavy metals (HMs) pose serious threats to both human and environmental health and therefore, effective and low-cost techniques to remove HMs are urgently required. Here we report a facile Fe-tannin coating method for zero-valent iron (ZVI) including nanoparticles (nZVI) and foam (Fefoam ), and demonstrate that the generated Fe-tannin coating would remove the inherent passive iron oxide shell of ZVI and provide channels for the galvanic replacement reaction between ZVI and HM ions. Electrochemical characterizations demonstrate that the Fe core of the modified ZVI materials could be easily oxidized and transfer electrons to HM ions owing to the facile mass transport and charge transfer. In 40 min, nZVI@Fe-TA exhibits excellent performances for Cd(II), Ni(II), Pb(II), Hg(II), Cu(II) and Cr(VI) removal, with the apparent removal rate constants of 0.083, 0.085, 0.083, 0.073, 0.092 and 0.078 min −1, respectively. It is found that the surface area normalized rate constants of nZVI@Fe-TA are 4–7 times higher than that of nZVI@Fe2 O3 counterpart, suggesting that the improved HM removal reactivity of nZVI@Fe-TA is derived from the surface modification. Moreover, nZVI@Fe-TA has advantages in resisting interference and in the simultaneous removal of different HM ions. Under a 30 min hydraulic retention time, Fefoam @Fe-TA could remove 98% HMs in the successive process. For real electroplating wastewater, Fefoam @Fe-TA exhibits excellent performance for Cr(VI) and Ni(II) removal, producing effluent of stable quality that meets local emission regulation. This study provides a facile strategy to remove the inherent passive iron oxide shell and enhance the HM removal reactivity for ZVI materials. Highlights: Fe-tannin-network coating would remove the inherent passive iron oxide shell of ZVI. Fe-tannin-network coating would accelerate the mass transport and charge transfer on the surface of ZVI. ZVI with Fe-tannin-network coating was fabricated by a facile assembly approach. Fefoam @Fe-TA could efficiently remove HMs in the successive process, achieving stable effluent.